Construction of Strict Fuzzy Exponential Distributions: Triangular and Trigonometric Methods - Abed, Youssef Prince; Ahmed, Abdul Hadi Nabih; Ramadan, Elshimaa (Mathematics and Computer Science: Research Updates Vol. 1, 2025)
This study introduces an innovative approach to constructing strict fuzzy membership functions from classical fuzzy membership functions, applying this technique to triangular and trigonometric distributions.